Synthesis and characterization of hybrid polyimide composites containing Octaphenyl-POSS by simple physical blending method. Issue 1 (24th July 2022) - Noh, Ji-Young; Lee, Seung-Hun; Park, No-Hyeong; Kim, Ki-Young; Lim, Jung-Hyurk; Kim, Kyung-Min
Abstract: A series of hybrid polyimide composites containing Octaphenyl-POSS (OPS) were prepared by the simple physical blending of aromatic 1, 3-bis(4-aminophenoxy)benzene (APB)-3, 3', 4, 4'-benzophenonetetracarboxylic dianhydride (BTDA) (APB-BTDA PI) and OPS. To improve the miscibility of OPS with PI matrix, poly(amic acid) (PAA) solution containing OPS was thermally imidized with different contents of OPS to synthesize OPS-PI hybrid composites. The incorporation of OPS into PI matrix through the simple blending method results in obtaining OPS-PI hybrid composites with lower dielectric constant and coefficient of thermal expansion (CTE). The obvious phase separation and uneven surface morphology caused by the aggregation of OPS in PI matrix were observed in 7.5 and 10 wt% OPS-PI.